The Impact of Good Governance and E-Governance on Public Trust in Bureau for Press, Media and Information, Secretariat of the President, Ministry of State Secretariat, the Republic of Indonesia - Noviandi, Holid; Suwaryono , Ixora Lundia (International Journal Labs, 2025)
This study analyzes the impact of good governance and e-governance on public trust in the Bureau for Press, Media, and Information (BPMI), Presidential Secretariat, Ministry of State Secretariat of the Republic of Indonesia. A quantitative approach was used, surveying 115 respondents involved in public information services. The findings show a strong positive correlation between good governance and public trust (r = 0.844), and a significant correlation between e-governance and public trust (r = 0.660). The combined effect of good governance and e-governance accounts for 72.6% of the variance in public trust. This indicates that effective implementation of transparency, accountability, and digital service innovations through e-governance significantly enhances public trust in the institution. Furthermore, e-governance accelerates the flow of information and improves public perception of the integrity and professionalism of BPMI. These results emphasize the importance of combining good governance with digital innovations to consistently strengthen public trust in governmental institutions.